ANALISA KEBIJAKAN ABORSI DI AMERIKA SERIKAT DI MASA PEMERINTAHAN BARACK OBAMA PADA TAHUN 2009-2013 - Halifa Haqqi, Clement Horatio Bundang, Setyasih Harini & (Transformasi, 2016)
On the year of 2008, Barack Obama make the abortion as one of his campaign issuees thepresident of United States. Based on the George W Bush era as the United States presidentbefore him,George W Bush makes the abortion is the illegal issues. But when Barack Obamawas elected became the president of United States he knows that he must keep his campaignissues become real, the abortion itself is an issue that is difficult to implement because the prosand cons attached to them, so the authors argue that it is feasible to study the process ofimplementing the policy of abortion in the US. Based on the theory system , the authors wantedto explain the reason for any reason that causes Barack Obama took any measures to legalizethe act of abortion. This research was conducted with a qualitative description of the approachand use data object of policy analysis abortions during the reign of Barack obama years 2009-2013 This study uses secondary data sources in the form of literature articles, online media andother sources relating to research.The reasons Barack Obama took the decision legal abortionenacted in the US in 2009 based on input which contains the support and demand which hasimpact on positive and negative things, and the output which is the result from the action or thepolicy that Barack Obama takes and the feedback to input and environment from the people ofUnited states. To reduce the number of abortions authors suggest :the government providesrules as to the terms of abortion, providing limit to the number of abortions, the governmentshould pay attention as pregnancy rates in the wwanita as to reduce the number of pregnanciesin women in the us government should pay more attention as the increase in family planningprogramsKey word : barack obama, abortion, theory system